2021
DOI: 10.1038/s41523-021-00243-7
|View full text |Cite
|
Sign up to set email alerts
|

The human intermediate prolactin receptor is a mammary proto-oncogene

Abstract: The hormone prolactin (PRL) and its receptor (hPRLr) are significantly involved in breast cancer pathogenesis. The intermediate hPRLr (hPRLrI) is an alternatively-spliced isoform, capable of stimulating cellular viability and proliferation. An analogous truncated mouse PRLr (mPRLr) was recently found to be oncogenic when co-expressed with wild-type mPRLr. The goal of this study was to determine if a similar transforming event occurs with the hPRLr in human breast epithelial cells and to better understand the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 48 publications
(49 reference statements)
0
34
0
Order By: Relevance
“…The participation of the ERα-c/EBP-Sp1 complex at the human PIII promoter region stimulates PRLR transcription/expression independently of estradiol [ 26 , 31 ]. In addition to the role of the predominant long form of PRLR in breast cancer, recently it has been shown that the human intermediate PRLR (alternatively spliced isoform) is a mammary proto-oncogene capable of stimulating cell survival and proliferation [ 40 ]. The oncogenic effect of intermediate PRLR isoform reaches to its full potential when expressed in concert with PRLR long form in MCF-10A cell lines.…”
Section: Prlr Signaling Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…The participation of the ERα-c/EBP-Sp1 complex at the human PIII promoter region stimulates PRLR transcription/expression independently of estradiol [ 26 , 31 ]. In addition to the role of the predominant long form of PRLR in breast cancer, recently it has been shown that the human intermediate PRLR (alternatively spliced isoform) is a mammary proto-oncogene capable of stimulating cell survival and proliferation [ 40 ]. The oncogenic effect of intermediate PRLR isoform reaches to its full potential when expressed in concert with PRLR long form in MCF-10A cell lines.…”
Section: Prlr Signaling Pathwaymentioning
confidence: 99%
“…Heterodimers of long and intermediate PRLR isoforms displayed greater stability than PRLR long form homodimers. These can activate JAK2/RAS/MAPK pathway, but unable to induce STAT5A phosphorylation [ 40 ].…”
Section: Prlr Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Assessments should consider interactions of PRL with other factors that affect BC such as estrogen and progesterone, the effects of PRL variants, and the relative expression of different PRLR isoforms. Notably, it has been recently reported that the intermediate isoform of the PRLR, which can hetero-dimerize with the long isoform, acts as a proto-oncogene in breast cancer [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that secretion of prolactin also occurs outside the pituitary gland, namely by the endometrium, lymphocytes, decidual membrane, breast, and prostate. In these organs, PRL has cytokine-like properties, binds to PRL-R on the cell surface and cytoplasm, and activates the signaling pathways Jak2/Stat5 and Map Kinase [4,5].…”
Section: Introductionmentioning
confidence: 99%